Learning Technology for Education Challenges 10th International Workshop, LTEC 2022, Hagen, Germany, July 11-14, 2022, Proceedings - Uden, Lorna; Liberona, Dario (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 10th International Workshop on Learning Technology for Education Challenges, LTEC 2022, held in Hagen, Germany, in July 2022. The 14 revised full papers and 6 short papers presented were carefully reviewed and selected from 41 submissions. The papers are organized in the following topical sections: learning methodologies and pandemic impact; learning practices and methodologies; learning technologies; learning technologies performance; serious games and virtual learning environments. .
Learning Methodologies and Pandemic Impact -- Learning Practices and Methodologies -- Learning Technologies -- Learning Technologies Performance -- Serious Games and Virtual Learning Environments. .
Keywords: Education-Data processing; Application software; Social sciences-Data processing; Database management; Artificial intelligence; Computers and Education; Computer and Information Systems Applications; Computer Application in Social and Behavioral Sciences; Database Management; Artificial Intelligence